2015
DOI: 10.1042/bsr20150197
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan metabolism, disposition and utilization in pregnancy

Abstract: SynopsisTryptophan (Trp) requirements in pregnancy are several-fold: (1) the need for increased protein synthesis by mother and for fetal growth and development; (2) serotonin (5-HT) for signalling pathways; (3) kynurenic acid (KA) for neuronal protection; (4) quinolinic acid (QA) for NAD + synthesis (5) other kynurenines (Ks) for suppressing fetal rejection. These goals could not be achieved if maternal plasma [Trp] is depleted. Although plasma total (free + albuminbound) Trp is decreased in pregnancy, free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
166
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(180 citation statements)
references
References 126 publications
(177 reference statements)
10
166
0
4
Order By: Relevance
“…The development of the fetuses with gestational age was accompanied by a higher synthesis and utilization of neurotransmitters, despite a similar availability of precursors which may reflect the increased fetal distress by malnutrition with time of pregnancy (Holden, 2007; Badawy, 2015). Most of the offspring coped with the situation but the fetuses affected by growth‐retardation evidenced altered neurotransmitters pathways at both catecholamines and indoleamines systems.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the fetuses with gestational age was accompanied by a higher synthesis and utilization of neurotransmitters, despite a similar availability of precursors which may reflect the increased fetal distress by malnutrition with time of pregnancy (Holden, 2007; Badawy, 2015). Most of the offspring coped with the situation but the fetuses affected by growth‐retardation evidenced altered neurotransmitters pathways at both catecholamines and indoleamines systems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the present study revealed several unexpected, tissue-specific metabolic features and other previously unrecognized downstream effects of TDO and IDO elimination. These effects shed new light on the regulation of the KP, which metabolizes the vast majority of dietary tryptophan in mammals (50), and have added relevance due to the fact that a number of KP metabolites have distinct, biologically significant properties (14,5153). Notably, we found no evidence that IDO can substitute for TDO in the absence of the latter or, conversely, that TDO performs IDO-like functions in Ido −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…TRP levels are also raised in the fetal brain when pregnant rats are stressed by crowding during the final week of gestation [38], though, to our knowledge, this effect has so far not been authenticated in mice. Although the underlying mechanism(s) may also include compensatory down-regulation of other TRP-degrading placental enzymes during the prenatal period [39] and/or direct effects of steroid hormones on TRP metabolism [4042], the elevated TRP levels seen in the highly vascularized placenta [43] immediately after restraint of the dam were more likely related to increased free TRP or to the presence of maternal blood where we observed a trend toward increased TRP levels (Table 2). …”
Section: Discussionmentioning
confidence: 99%
“…KP metabolites and enzymes, too, may play a role in the placenta both under physiological conditions and when the organ is compromised [32,50–53]. Notably, as both TRP and KYN pass easily from the placenta to the fetus [42,51,54,55], the transient increases in the fetal levels of these two compounds seen here in response to maternal stress may be at least in part caused by direct transfer from the placenta. KYNA, in contrast, does not penetrate readily from the placenta into the fetus [55], i.e.…”
Section: Discussionmentioning
confidence: 99%